Isolation, Identification of Bacterial Species Causing Chronic suppurative Otitis Media and Detection Some of Their Virulence Factors - Yumna Shaker Mahmood; Suha Maher Abed; Amar Mohammed Alwan (Tikrit Journal of Pure Science)
The study is conducted to diagnose the aerobic bacterial species causing chronic suppurative otitis media (CSOM), reveal the antibiotic susceptibility pattern and detect some of their virulence factors. Samples were collected during the period from June till December 2018.  From a total of eighty-two patients admitted to Samarra Hospital and outpatient clinics of both genders with different age groups, 82 bacterial culture are recovered using a cotton swab. Identification of bacterial isolates is performed depending on micro and macroscopic cultural characteristics and biochemical tests. Results of the current work show that the highest infection rates are at the age groups >1 to 5 and 11 to 20 years by (20%). Among eight bacterial species isolated in the current study (S. aureus, P. aeruginosa, K.pneumonia, S.epidermidis, E.coli, P.vulgaris, C. freundii, E. Cloacae), S. aureus had scored the highest rate (41%) of the total infections while the lowest rate was scored by E.Cloacae(1%). The antibiotic sensitivity test suggests that almost all isolates were sensitive to ciprofloxacin and meropenem (96% and 94% respectively) while they were resistant to Cefixime. The ability of bacteria is isolated from CSOM to produce biofilm and some virulence factors (gelatinase, hemolysin, DNase, urease) are investigated the virulence factor results revealed that. S. aureus, P.aeruginosa, K. pneumonia had the ability to produce biofilm and S. aureus, P. aeruginosa  have the ability the highest production for the majority of virulence factors.